(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The scientific-theoretical and legal basis of the formation of state budget revenues, the economic essence, importance and characteristics of direct taxes, the issues of increasing the role of direct taxes in the formation of state budget revenues are revealed.